Data on the population of reduced earnings capacity-pensioners in Germany: 2001-2020 - Katharina Werhan (Journal of Economics and Statistics, 2023)
Pensions for reduced earnings capacity (REC) have yearly made up about 20% of all pensions granted by the German Pension Insurance in the past 25 years. The dataset described in this article is a time series of cross-sectional observations for the retirement cohorts 2001-2020. It enables researchers to have a detailed insight into the population of REC-pensioners and allows observing trends and effects of reforms over time. The article provides general information on the data, first descriptive analyses, examples on possible matching with other data of the FDZ-RV and information on how to access the data.
Keywords: H55; J26; 330; administrative data; pensions; reduced earnings capacity; time series